Capacities of atrial fibrillation detection after stroke: a French nationwide survey. (14th October 2021) - Guidoux, C; Sibon, I; Alamowitch, S; Godeneche, G; Guillon, B; Timsit, S; Sablot, D; Cordonnier, C; Tardy, J; Granier, M; Extramiana, F; Cohen, A; et al.
Abstract: Background: Atrial fibrillation (AFib) is a major contributor to recurrent but preventable ischemic Stroke (IS)/TIA. However, majority of stroke patients suffer from paroxysmal asymptomatic AFib, which implies stroke health system to implement accurate AFib detection strategies to large scale population. Current practices of AFib screening methods provided by Stroke Units (SU) organization and network in France are currently unknown and uncovered by dedicated guidelines. Purpose: To assess the methodology of Afib screening in French SU. Methods: A French Nationwide survey was led (September-November 2020) with on-line structured questionnaires sent to individual targeted stroke-physicians (SP) and heads of SU in France.We analyzed qualitative and quantitative availability and current use of AFib detection tools during acute inhospital and outpatient subacute and chronic post-IS phases. Results: 67% of 140 heads of SU and 33% of SP responded across all continental and overseas French regions.Main clinical characteristics that lead to search Afib are: TIA/IS recurrence under antiplatelet therapy (97%), patient's age (74%), proximal occlusion of a major cerebral artery (72%). Afib is highly suspected when there is: recent brain IS in multiple vascular territories (100%), previous IS in another vascular territory (98%), left atrial enlargement (96%), burst of supraventricular tachycardia <30s (94%). In-hospital cardiac monitoring is considered to be mandatory by 90% of SU teams but only 1/3 of those possess telemetry out of intensive care unit. Outpatient cardiac monitoring is considered of major interest/necessary by 100% of SP. When first line 24-hour Holter monitor is normal and Afib is highly suspected, 75% of the SP required outpatient noninvasive monitoring (NIM) for at least 7 days and more than half required insertable cardiac monitor (ISC). ISC are implanted each year by SU for <10 patients in 44% and <50 patients in 94%. The delay IS-ICM implantation is <1 month in 10%, 1–3 months in 52%, 3–6 months in 29% and >6 months in 9%. Accessibility to outpatient monitoring modalities is graded: fairly easy for 24/48h-Holter (85%) and ISC (68%); rather difficult/impossible for 3–7 days NIM (51%), 8–21 days NIM (75%) or e-ECG tools (99%). Main obstacles to monitoring abilities development in SU were lack of: manpower (80%), efficient network with cardiologists (56%), familiarity of techniques (42%); and technical equipment cost (44%). 96.5% of SU teams deem necessary practice decision support flowchart with cardiologist partnership but 19% use for it. Conclusion: The survey raises concern about lack of a systematic strategy and shortcomings for Afib detection capacities. These results are a call to establish practice-guidelines and to promote an improvement plan for AFib detection (selection of the patients, tools and prioritization of the exams) after TIA/IS in France which will require a strong collaboration between neurologists and cardiologists. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): BMS-Pfizer